Cognitive Efficacy (SIB) of 13.3 Versus 4.6 mg/24 h Rivastigmine Patch in Severe Alzheimer's Disease. (May 2016) - Isaacson, Richard S.; Ferris, Steven; Velting, Drew M.; Meng, Xiangyi
Severe Impairment Battery (SIB) data from the 24-week, randomized, double-blind ACTivities of daily living and cognitION (ACTION) study suggest that patients with severe Alzheimer's disease (AD) benefit from treatment with 13.3 versus 4.6 mg/24 h rivastigmine patch. The objective of this retrospective analysis was to further examine the cognitive efficacy of 13.3 versus 4.6 mg/24 h rivastigmine patch on individual SIB items, and SIB domains derived using factor analysis of these items. Change from baseline at Week 24 on 9 new factor-defined domains and individual items was calculated and compared using effect sizes (Cohen's d). Numerically less decline was observed with 13.3 versus 4.6 mg/24 h patch on all domains and the majority of individual items. Largest least squares mean treatment differences were observed on "visuospatial reasoning, " "object naming, " "recognition, " "design copying, " "social agency, " "ideational praxis, " and "comprehension" domains. These findings suggest 13.3 mg/24 h rivastigmine patch demonstrates broad cognitive efficacy across a range of SIB items and domains in patients with severe AD.